ANALISIS BREAK EVEN POINT SEBAGAI DASAR PERENCANAAN LABA PADA UD. YAPHIN SNACK KARANG BANGUN KECAMATAN SIANTAR KABUPATEN SIMALUNGUN - Arshandy, Eliza; Ervina, Nelly; Siregar, Liper; Eka Putri, Debi; Tondang, Claudia J (LP2M Universitas Perjuangan Tasikmalaya, 2024)
ABSTRACT. The aims of this study were: 1. To find out the description of the break even point as the basis for planning onion cake profits at UD. Yaphin Snack Karang Bangun, Siantar District, Simalungun Regency. 2. To find out the break even point as a basis for planning onion cake profits at UD. Yaphin Snack is located in Karang Bangun, Siantar District, Simalungun Regency. This research was conducted using qualitative descriptive analysis methods and inductive analysis. The types of data used in this study are qualitative data and quantitative data. Sources of data used in this study are primary and secondary data. The results of this study can be summarized as follows: 1. Fixed costs from 2017 to 2021 have not changed. 2. Raw material costs from 2017 to 2019 have increased 3. Direct labor costs have not increased except for the printing part. 4. Variable costs from 2017 to 2019 have increased. 5. Factory overhead costs from 2017 to 2019 have increased. 6. Production data for 2017 to 2019 has increased. 7. The break even point from 2017 to 2019 has increased. 8. The level of sales margin of safety from 2017 to 2019 has increased, but in 2020 it has decreased.